2021
DOI: 10.1093/bioinformatics/btab305
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-based membership inference from summary genomic data

Abstract: Motivation The availability of human genomic data, together with the enhanced capacity to process them, is leading to transformative technological advances in biomedical science and engineering. However, the public dissemination of such data has been difficult due to privacy concerns. Specifically, it has been shown that the presence of a human subject in a case group can be inferred from the shared summary statistics of the group, e.g. the allele frequencies, or even the presence/absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Beacon-responses are supplemented with phenotype metadata, and the attacker already knows about an individual's membership. Bu and colleagues [3] introduced a haplotype-based membership inference attack that reconstructs haplotypes using allele frequencies, as opposed to relying on a target genome. Samani and colleagues [16] introduced am method that relied on high-order SNV correlations to carry out an inference attack on Beacons using Markov models.…”
Section: A Related Workmentioning
confidence: 99%
“…Beacon-responses are supplemented with phenotype metadata, and the attacker already knows about an individual's membership. Bu and colleagues [3] introduced a haplotype-based membership inference attack that reconstructs haplotypes using allele frequencies, as opposed to relying on a target genome. Samani and colleagues [16] introduced am method that relied on high-order SNV correlations to carry out an inference attack on Beacons using Markov models.…”
Section: A Related Workmentioning
confidence: 99%
“…Further studies identified that participation in different studies can lead to linking attacks and reveal sensitive information [42,43] of participants and relatives [44,45]. Other attacks that make use of haplotype frequencies have been proposed to identify participation [46,47]. Recent studies demonstrated that genetic beacons [48] (where the existence of variants in a database are queried as yes/no answers) are vulnerable to Bustamante's attacks [49] and more advanced attacks [50,51] where an adversary can identify participation of an individual in a beacon by adversarial querying, which may impact biobank scale databases.…”
Section: Introductionmentioning
confidence: 99%
“…Further, populationlevel omics (e.g., population genomics) hold tremendous potential for classifying individuals based on allelic diversity and identifying genetically-related individuals (Lippert et al, 2017). Such strategies can help calculate homozygosity and inbreeding coefficients (Ghoreishifar et al, 2020;Sumreddee et al, 2021) for designing appropriate breeding programs to maintain genetic diversity and avoid inbreeding depression (Alemu et al, 2021;Bu et al, 2021). However, while many WGS databases and consortiums have been formed in humans (Zhang et al, 2018) (GenomeAsia 100K Consortium, 2019, no high-resolution database of population-level genetic variants is available for animals.…”
Section: Introductionmentioning
confidence: 99%